Immigrant nurses' perceptions on cultural differences‐based job concerns: A phenomenological study in Shanghai China. Issue 17 (6th February 2018) - Yu, Haiping; Peng, Youqing; Hung, Yunying; Zhou, Lin
Abstract : Aims and objectives: To explore the experiences of immigrant nurses working in Shanghai, China. Background: With the development of China, population growth has been accelerating. Simultaneously, the number of immigrant nurses in Shanghai has been increasing dramatically. Meanwhile, their turnover rate is abnormally high, primarily because of job concerns stemming from cultural differences. An understanding of immigrant nurses' job concerns caused by cultural differences can be used to help them to work more efficiently and cohesively. We aimed to investigate immigrant nurses' lived experiences regarding job concerns caused by cultural differences in Shanghai, China. Methods: This is a phenomenological study. In‐depth semi‐structured interviews were conducted with fifteen immigrant nurses from January–July 2016. Data were collected using audio‐taped face‐to‐face interviews; the narratives were then transcribed verbatim and analysed thematically. Results: The following three major themes emerged from the data: "communication difficulties, " "work adjustment difficulties" and "life adjustment difficulties." The eight sub‐themes within these were as follows: (i) language barrier, (ii) inability to integrate oneself with the local culture, (iii) feelings of unfairness, (iv) difficulty asking for leave, (v) feeling stressed, (vi) not being acclimatised, (vii) feeling helpless and (viii) feeling guilt at being unable to take care of their family. Conclusion: It is important to implement appropriate training programmes on language and cultural adaptation for immigrant nurses. To enhance integrate immigrant nurses into Shanghai's society, more support needs to be provided. Relevance to clinical practice: Administrators in hospitals should pay attention to immigrant nurses' job concerns that are caused by cultural differences and provide timely and effective assistance.